A Content Analysis of External Risk Reporting in UK Public Telecommunications Companies - Liu, Yuting (2006)
This research paper examines and compares risk information disclosures in the annual reports of UK telecommunications companies for the financial year of 2001/02 and 2005/06. Following a content analysis, risk information contained in the company annual reports are classified according to their risk categories and characteristics. Increases in both voluntary and mandatory disclosures are found, although there is still a lack of clarity and measurability. The risk information does not get reported in a consistent and comprehensive way. Therefore, the usefulness of risk disclosure does not appear to be improving. The author concludes that it might be desirable to let investors drive the direction of future developments of risk disclosure. This may be better achieved within a voluntary disclosure environment with supports from risk management associations of individual business sectors. Corporate web site could potentially be a better place to locate risk disclosure.